UJI KESESUAIAN BERKAS SINAR-X DENGAN BERKAS KOLIMATOR PADA PESAWAT SINAR-X DI INSTALASI RADIOLOGI RSUD RADEN MATTAHER JAMBI - Enggel Fransiska; Nehru Nehru; Muhammad Ficky Afrianto (Universitas Riau, 2018)
The collimator test is one of the X-ray Quality Control (QC) program, one of the central point beam testing and the area of the collimator beam using the RMI unit. The purpose of the collimator test is to find out the suitability of the broad field of collimator with the area of X-ray beam in tolerance of ≤ 2% Focus Film Distance (FFD) and the correspondence of the X-ray center point in tolerance Ɵ = 3˚ as determined by the Minister of Health Decree No . 1250 / SK / XII / 2009. The study was conducted using variations of FFD at 100 Cm, 90 Cm, 80 Cm, on three X-ray radiation radiology radiation RSUD Raden Matther Jambi. In this study using digital radiograph unit (DR) or computed radiographaphy, no longer using conventional radiographs such as previous studies. Irregularities or wide discrepancies in the area of the X-ray beam are evaluated by evaluating the firm boundary of the line formed by the X-axis and Y-axis, then determining the midpoint between the line boundary and the radiation boundary of the scatter. The deviation results concluded that there was no deviation at the central point of X-ray beam for all X-ray aircraft tested by all aircraft still within the tolerance threshold Ɵ = 3˚. But for the value of the collimator area all the X-ray macine tested has deviations exceeding the predefined 2% FFD threshold where the radiologie france plane occurs deviation on the Y axis with FFD 90 Cm and 80 Cm, hyundai medicaly X- ray on X axis with FFD 100 Cm and 80 Cm, Y axis with FFD 80 Cm, and on villa sistei medicali SpA plane on X axis with FFD 80 Cm, Y axis at FFD 80 Cm.